AIDS: knowledge, skills and attitudes among vocational trainees and their trainers. - Brown-Peterside, P (1991)
In order to assess the adequacy of learning about the human immunodeficiency virus (HIV) and the acquired immune deficiency syndrome (AIDS) in vocational training for general practice, a postal questionnaire survey was carried out among trainers and their trainees in seven health regions of England and Scotland. A total of 616 trainers (62%) and 538 trainees (58%) responded to the questionnaire asking about their knowledge, skills and attitudes regarding HIV and AIDS. Trainees' principal difficulties with HIV and AIDS resembled those of general practitioners currently in practice. More than 60% of trainees lacked knowledge about HIV and AIDS in babies, 50% would not accept intravenous drug misusers onto their list, only 12% found it easy to discuss sex with homosexual male patients, and only 37% felt able to offer counselling about HIV and AIDS. Trainees who had had a tutorial on HIV and AIDS as part of vocational training were significantly more knowledgeable than the remainder (P less than 0.01). In addition, trainees who found workshops on HIV and AIDS useful were more willing than others to take on drug misusers (P less than 0.05) and more confident in their ability to counsel patients with HIV infection (P less than 0.01). No significant associations were found between the trainers' own knowledge, attitudes and skills regarding HIV and AIDS and those of their trainees. It is concluded that there is a need to improve teaching about HIV and AIDS in vocational training for general practice. All general practitioner trainees should receive a tutorial to update their knowledge about HIV and AIDS, and attend a suitable workshop to challenge unfavourable attitudes and improve confidence in counselling.